The Influence of Pile-Driving Vibration on the Soil Nailing Support of a Silty Soil Foundation Pit. (19th May 2021) - Guo, Yuancheng; Wu, Hao; Li, Chenglin
Abstract : The ground vibration induced by pile driving affects the safety of the adjacent foundation pit. In this paper, the influence of pile-driving vibration on the soil strength and the nail-soil interface strength was studied, and the variation in the axial force and displacement of the soil nail under vibration was analyzed. The paper studied the effects under different vibration parameters on the soil strength and the nail-soil interface strength by using a vibration exciter and a nail pull-out model box. The results showed that the stronger the excitation force was and the higher the frequency was, the greater the attenuation of the soil strength and nail-soil interface strength was. On the contrary, the change of the internal friction angle of the soil was not obvious under the vibration. The nail-soil interface strength recovered when the vibration terminated. Decreases in c and τ p led to an increase in the working length of the soil nail, a redistribution of the axial force, and an augmentation in the soil nail displacement.